Mapping And Positioning Of Learning Materials In Tourism Studies In Indonesia - Ida Ayu Suryasih; I Putu Anom; Ida Bagus Suryawan (Jurnal sosial dan sains, 2022)
Background: The debate about tourism science has entered a new chapter with the Declaration of Tourism Science on August 24, 2006 in Jakarta which states that based on various studies, tourism has met the requirements as a science based on the philosophy of science. Tourism has now developed into a subject of knowledge that deserves to be discussed scientifically to produce scientific knowledge (science). Purpose: the purpose of compiling study materials related to the existing science in the Tourism Study Program and determining the positioning of the study program compared to study programs related to existing tourism. This research is a follow-up to the determination of the nomenclature of tourism study programs in 2017 and 2019. Method: This research is located in a number of tourism destinations that have experienced different developments at each stage. The research will be conducted in the area of Bali Province as a tourist destination that has experienced a stage of development Results:. The development of teaching materials needs to be carried out systematically based on interrelated steps to produce useful teaching materials. Tourism in Indonesia has existed since the Dutch colonial era precisely since 1910-1920 with the issuance of a decree of the Dutch Governor General named VTV (Vereneiging Touristen Verker) the start of travel activities to the Dutch East Indies (Indonesia- present). The Field of Tourism Work according to the standard classification of Indonesian business fields (KLBI) in 2020 is included in the group of arts, entertainment and recreation. In general, the Decree of the Minister of Research, Technology and Higher Education of the Republic of Indonesia Number 257 / M / KPT / 2017 concerning the Name of the Study Program in Higher Education, study programs related to tourism are included in the group of applied science clusters. The scope of the study refers to tourism development efforts consisting of the development of tourism destinations, industrial development, marketing development and tourism institutional development. Related to the application of the scope of tourism studies, it is generally divided into 2 fields of education, namely vocational education and academic education. Conclusion : The scope of what study materials are used in learning tourism science in existing conditions is more about tourism planning, tourist trips and management of accommodation and restaurants. Tourism science consists of 3 main groups, namely policies, territories and tourism businesses. The scope is more about how tourists, local communities and tourist activities are carried out